Analisis Tingkat Pendapatan Keluarga dan Pelatihan Kewirausahaan Gender dalam Perspektif Ekonomi Islam - Heni Noviarita; Ari Kurniyawati; Nur Wahyu Ningsih; Weny Rosilawati (Jurnal Ilmiah Ekonomi Islam, 2021)
The purpose of this study was to find out the effect of entrepreneurial training on family income level in Islamic economic perspective. The research was motivated by low income levels in way sari village families, the majority of which are farmers. This research was conducted by quantitative method. The population in this study is way sari residents who have participated in entrepreneurship training of 130 participants, the number of samples in this study is 40 respondents. The data was collected using questionnaires and documentation of entrepreneurship training. The data obtained through the questionnaire was analyzed using a simple regression test. Data analysis shows that there is an increase in income in individuals after attending entrepreneurship training.